Obstructive sleep disordered breathing – multidisciplinary management with a particular focus on the role of an orthodontist - Burghard, Marcin; Brożek-Mądry, Eliza; Krzeski, Antoni (Forum Ortodontyczne / Orthodontic Forum, 2019)
Obstructive Sleep Disordered Breathing (SDB) is a common clinical problem that refers to a few percent of population. If undiagnosed, it constitutes a significant risk and it is associated with many consequences. According to current views and classification, the Obstructive Sleep Apnea Syndrome (OSAS) is the most dangerous clinical form of the obstructive SDB. A problem relates not only to adults, but also to children. There are many epidemiological and pathophysiological differences between aforementioned groups of patients. The management is also different. There are also similarities – high percentage of undiagnosed and/or untreated cases. Currently, necessity of multidisciplinary approach to discussed disorders is recommended as well as involvement of: laryngologists, pulmonologists, orthodontists, maxillofacial surgeons, internal medicine specialists, pediatricians, and general practitioners. Aim. The aim of this paper is to systematize knowledge on the obstructive SDB in children and adults in the face of rapid progress in knowledge in recent years, to point out therapeutic options provided by various specialists, with particular focus on orthodontists, and to highlight differences in therapy of children and adults. Material and methods. Conservative and surgical methods of OSAS treatment were described, options of orthodontic management were listed, and various age groups were reviewed. Results. It should be considered to recommend weight loss and modification of some habits. Effective conservative methods of OSAS treatment include: nasal steroids, montelukast, air prosthesis, myofunctional therapy. Important elements of surgical treatment include: adenotonsillectomy (especially in children), orthognathic surgery, and eventually – tracheotomy. Orthodontic management should include: rapid maxillary expansion (also with surgical support), facemask therapy, and functional devices for advancing the mandible. Conclusions. Patients suffering from the discussed problem require multidisciplinary care, and an orthodontist is a very important link. (Burghard M, Brożek-Mądry E, Krzeski A. Obstructive sleep disordered breathing – multidisciplinary management with a particular focus on the role of an orthodontist. Orthod Forum 2019; 15: 58-67).